Evaluation of the potential of coastal cliffs as geosites for the promotion of geotourism - Fernando Morante-Carballo; María José Domínguez-Cuesta; Nataly Paz-Salas; Jenifer Malavé-Hernández; Jairo Dueñas-Tovar; Paúl Carrión-Mero (Geography and Sustainability, 2023)
Coastal zones, with their significant geodiversity, are vital areas for geotourism. Effective management is crucial to harness the geological interest of these sites as geotourism resources while ensuring their conservation. Manabí Province is one of the most representative regions along the Ecuadorian coast due to its beaches and coastal cliffs, offering a wealth of tourist attractions and cultural elements. This study aims to evaluate the geosite potential of six cliffs in Manabí Province through quantitative and qualitative analyses to propose geotourism promotion strategies. The methodology involves (i) inventory and characterisation of the cliffs, (ii) assessment of the sites by the Spanish Inventory of Places of Geological Interest method (IELIG), and (iii) qualitative evaluation through focus group discussions and Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. The results reveal that all six sites boast diverse geological assets, including geomorphological, stratigraphic, sedimentological, and tectonic elements. They are characterised by “high” scientific, didactic, and tourist interest, while also being susceptible to degradation due to natural and anthropic threats. The SWOT analysis demonstrates that the valuable geological and geomorphological heritage of potential geosites provides an opportunity to foster geotourism and boost the province’s economy, incorporating geoconservation and geoeducation strategies. This study proposes a georoute called “Ruta Acantilados del Sol”, a 245 km journey encompassing all six sites, incorporating diverse tourist and cultural activities. Our research lays the foundation for fostering geotourism along the Manabí coast and strengthening the connection between nature, heritage, and the welfare of residents within a global resilience plan.